The spatial transcriptome of the late-stage embryonic and postnatal mouse brain reveals spatiotemporal molecular markers - Yuichiro Hara; Takuma Kumamoto; Naoko Yoshizawa-Sugata; Kumiko Hirai; Xianghe Song; Hideya Kawaji; Chiaki Ohtaka-Maruyama (Scientific Reports)
Abstract The neocortical development process includes cell proliferation, differentiation, migration, and maturation, supported by precise genetic regulation. To understand these processes at the cellular and molecular levels, it is necessary to characterize the fundamental anatomical structures by gene expression. However, markers established in the adult brain sometimes behave differently in the fetal brain, actively changing during development. The spatial transcriptome is a powerful analytical method that enables sequence analysis while retaining spatial information. However, a deeper understanding of these data requires computational estimation, including integration with single-cell transcriptome data and aggregation of spots at the single-cell cluster level. The application of such analysis to biomarker discovery has only begun recently, and its application to the developing fetal brain is largely unexplored. In this study, we performed a spatial transcriptome analysis of the developing mouse brain to investigate spatio-temporal regulation of gene expression during development. Using these data, we conducted an integrated study with publicly available mouse data sets. Our data-driven analysis identified novel molecular markers of the choroid plexus, piriform cortex, and thalamus. Furthermore, we identified a novel molecular marker that can determine the dorsal endopiriform nucleus (DEn) of the developmental stage in the claustrum/DEn complex.